Adaptation in human immune cells residing in tissues at the frontline of infections - Irepan Salvador-Martínez; Jesus Murga-Moreno; Juan C. Nieto; Clara Alsinet; David Enard; Holger Heyn (Nature Communications)
Abstract Human immune cells are under constant evolutionary pressure, primarily through their role as first line of defence against pathogens. Most studies on immune adaptation are, however, based on protein-coding genes without considering their cellular context. Here, using data from the Human Cell Atlas, we infer the gene adaptation rate of the human immune landscape at cellular resolution. We find abundant cell types, like progenitor cells during development and adult cells in barrier tissues, to harbour significantly increased adaptation rates. We confirm the adaptation of tissue-resident T and NK cells in the adult lung located in compartments directly facing external challenges, such as respiratory pathogens. Analysing human iPSC-derived macrophages responding to various challenges, we find adaptation in early immune responses. Together, our study suggests host benefits to control pathogen spread at early stages of infection, providing a retrospect of forces that shaped the complexity, architecture, and function of the human body.